Women's empowerment in agriculture: Implications for technical efficiency in rural Bangladesh - Seymour, Gregory (Wiley, 2017)
Although a great deal of research exists on gender and agriculture, few studies investigate the implications of reduced gender disparities in households for technical efficiency. In this article, I compare the levels of technical efficiency achieved on plots operated by households with different levels of gender disparities. Using plot‐level data from the 2011–2012 Bangladesh Integrated Household Survey and drawing on indicators derived from the Women's Empowerment in Agriculture Index, I estimate a stochastic frontier production function model, which includes women's empowerment in agriculture as an exogenous determinant of technical inefficiency. I find that reduced gender disparities within households (measured in terms of the empowerment gap between spouses) are associated with higher levels of technical efficiency. This result extends to plots that women jointly manage with their spouses, as well as those that women do not actively manage.